2005
DOI: 10.1097/01.prs.0000152419.76354.67
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Study of Sonographically Assisted Percutaneous Release of the A1 Pulley

Abstract: The purpose of this study was to assess the value of using intraoperative sonography to assist percutaneous release of the A1 pulley in cadavers. By detailed sonographic examination and anatomical exploration, the authors determined the correlation of the actual A1 and A2 pulleys (and adjacent neurovascular bundles not visualized by sonography) to the clearly visualized flexor tendons and the metacarpophalangeal joint. The authors also evaluated their effectiveness as landmarks and the effectiveness of real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 20 publications
9
74
3
1
Order By: Relevance
“…Whilst the results of their study were encouraging with no reported complications, they used a customised hook knife to perform the release that is not readily available and would represent an added expense of the procedure ($15 per knife) [4]. In contrast, we used a modified 19-gauge (white) needle as the cutting device which is cheap, widely available and used for blind percutaneous release of the annular pulley [3,8,13,16,20,23,27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Whilst the results of their study were encouraging with no reported complications, they used a customised hook knife to perform the release that is not readily available and would represent an added expense of the procedure ($15 per knife) [4]. In contrast, we used a modified 19-gauge (white) needle as the cutting device which is cheap, widely available and used for blind percutaneous release of the annular pulley [3,8,13,16,20,23,27,28].…”
Section: Discussionmentioning
confidence: 96%
“…All 107 digits were successfully treated, postoperative recovery was uneventful and there were no recurrences during an average 12.5 month follow-up. Sonography was able to show the several landmarks for the division procedure and depict the instruments and the target structures simultaneously during the operation for our cadaver study (Chern et al, 2005) and this clinical study. The safety of sonographically assisted, percutaneous release has been demonstrated by the absence of iatrogenic digital nerve injury in any of these digits.…”
Section: Article In Pressmentioning
confidence: 98%
“…Although most trigger digits can be diagnosed straightforwardly by clinical presentation, the value of ultrasonographic imaging in determining pathologic structures remains encouraging. To date, there are limited data evaluating the clinical use of ultrasonography in trigger digit (Boutry et al 2005;Chern et al 2005;Gruber et al 2011;Guerini et al 2008;Kim and Lee 2010;Rajeswaran et al 2009;Serafini et al 1996;Tagliafico et al 2009), and the association between clinical presentation and severity grading has rarely been reported in the literature. Although severity grading is not universally used as a guide to plan treatment, a tool that could help physicians in correlating the clinical presentations is useful and welcome in the current context of patient-oriented and cost-effective medicine.…”
Section: Introductionmentioning
confidence: 96%
“…It has been an ideal imaging tool in the initial investigation of flexor digit tendons (Chern et al 2005;Khoury et al 2007;Klauser et al 2004;Lee et al 2000;Serafini et al 1996) and can be helpful in the evaluation of trigger digits. In trigger digit, ultrasonography can reveal effusion or abnormality of the flexor digit tendons and surrounding structures and impairment of tendon gliding.…”
Section: Introductionmentioning
confidence: 99%